Soil Improvement Method on Body Foundation Dam (Main Dam) with Grouting Method DAM Construction Project (Rababaka Kompleks, West Nusa Tenggara) - Hakim, Lutfi; Sari, Ribut Nawang; Sukatja (Journal of Global Engineering Research and Science, 2023)
Cement injection under pressure, also known as grouting, is a process in which a liquid mixture is injected into cavities, cracks, and fractures in rock or soil under controlled pressure. The injected liquid undergoes physical and chemical transformations, eventually solidifying. This study aimed to evaluate the performance of various cement-water mixture designs, determine the required volume of grout based on the Lugeon number (Lv), and assess effective spacing intervals between grouting points by calculating grout effectiveness in percentages. Jet grouting, a proven method in diverse soil conditions, employs specialized equipment to hydraulically mix soil with grout, enabling soil stabilization and modification. The system is particularly effective in erodible soils, such as granular soils, and even in cohesive plastic clays. At the Mila Dam, grouting tests were conducted along the centerline of the main dam, specifically at the left abutment (Bukit Tumpuan Kiri) and the riverbed. Core drilling results from the Pilot Hole (BH-01) at a depth of 30 m revealed stratigraphic characteristics. The left abutment rock along the centerline of the dam predominantly consists of gray lapilli tuff overlaid by breccia-tuff rock units, which are brownish in color.